Qualidade física do solo sob diferentes tempos de adoção e de escarificação do sistema plantio direto e sua relação com a rotação de culturas - Moraes, Moacir Tuzzin de (2013)
No-tillage (NT) is a tillage system more important for the sustainability of agro-ecosystems. However doubts remain concerning the formation of layers with high compaction level in NT, residual effects of soil chiseling, and alteration of soil structure during the time of adoption of NT. The objective of this study was to evaluate the effect of crop rotation, chiseling and periodic time of adoption of NT on the physical quality of a Rhodic Eutrudox, and productivity of soybean and wheat. The tillage systems were: (i) conventional tillage by disk harrow (CT); (ii) NT with chiseling every year (NTC1); (iii) NT with chiseling every three years (NTC3); (iv) NT for 11 consecutive years (NT11) and; (v) NT for consecutive 24 years (NT24) while the cropping factor include: (i) crop rotation and (ii) crop succession. Sampling was conducted 10 and 22 months after last chiseling in NTC1 and NTC3, respectively. Undisturbed soil samples were collected in soil layers, 0.0-0.10, 0.10-0.20 and 0.20-0.30 m for the determination of physical attributes (particle density and particle size distribution, bulk density, porosity, macro and micropores, soil penetration resistance (SPR), SPR curve, water retention curve, least limiting water range), while disturbed samples were used to quantify soil chemical properties (soil acidity, macronutrients, organic carbon, nitrogen). In the soil depth, 0.10 and 0.20 m, three-dimensional infiltration rate and saturated hydraulic conductivity were determined in-situ. At maturity, the productivity of soybeans and wheat was determined. There was no interaction between tillage and cropping system. The variables analyzed did not change as a function of the cropping systems. The chemical attributes were not limiting the productivity of soybeans. The physical attributes indicated that the residual effects of soil chiseling did not persist for longer than 10 months. Increasing the time of adoption of NT from 11 to 24 years favored improvements in soil physical quality. The NT24 had higher yield of soybeans than SPC. Chiseling did not result in increased productivity of soybeans and wheat compared with NT. The increased time without tilling the soil, in the same soil bulk density and water content favored increase in resistance of soil structure. Critical limits of SPR (2 MPa) are inadequate for the assessment of soil physical quality in NT with or without soil chiseling. These SPR limits should be expanded to 3 MPa in NT with chiseling and 3.5 MPa in NT. The least limiting water range, regardless of soil management, cropping system and critical limits of SPR was not a good indicator of soil physical quality.